Integração de um ambiente virtual de aprendizagem com aplicações móveis de suporte a educação a distância - Sarmento, Wellington Wagner Ferreira (2007)
This dissertation proposes an extension of the traditional concept of Learning Management System (LMS) – currently based on the Web technology – where it must act as an integration element for several media aiming the Distance Education process. As a first step heading to this purpose, a web service-based integration model is shown between the SOLAR environment of the web-based distance courses and a set of mobile education applications, which are developed with the intention of allowing an increase of the present resources in the used virtual environment. The model of integration is based in Web Services whom communicate with three educational mobile applications. This mobile applications extend a notify, communication and on field works services of a LMS. The justification of this effort is based on the pedagogic need of having more and more the interaction process.